Bone formation following implantation of titanium sponge rods into humeral osteotomies in dogs: A histological and histometrical study - Faria, Paulo Esteves Pinto; Carvalho, Alexandre Leite; Felipucci, Daniela Nair Borges; Wen, Cui'e; Sennerby, Lars; Salata, Luiz Antonio (My University, 2010)
Background: Titanium (Ti) is widely proven to enhance bone contact and growth on its surface. It is expected that bone defects could benefit from Ti to promote healing and to increase strength of the implanted area. Purpose: The present study aimed at comparing the potential of porous Ti sponge rods with synthetic hydroxyapatite (HA) for the healing of bone defects in a canine model. Material and Methods: Six mongrel dogs were submitted to three trephined osteotomies of 6.0 × 4.0 mm in one humerus and after 2 months another three osteotomies were performed in the contralateral humerus. A total of 36 defects were randomly filled either with Ti foam, particulate HA, or coagulum (control). The six animals were killed 4 months after the first surgery for histological and histometrical analysis. Results: The Ti-foam surface was frequently found in intimate contact with new bone especially at the defect walls. Control sites showed higher amounts of newly formed bone at 2 months - Ti (p = 0.000) and HA (p = 0.009) - and 4 months when compared with Ti (p = 0.001). Differently from HA, the Ti foam was densely distributed across the defect area which rendered less space for bone growth in the latter's sites. The use of Ti foams or HA resulted in similar amounts of bone formation in both time intervals. Nevertheless, the presence of a Ti-foam rod preserved defect's marginal bone height as compared with control groups. Also, the Ti-foam group showed a more mature bone pattern at 4 months than HA sites. Conclusion: The Ti foam exhibited good biocompatibility, and its application resulted in improved maintenance of bone height compared with control sites. The Ti foam in a rod design exhibited bone ingrowth properties suitable for further exploration in other experimental situations. © 2008, Copyright the Authors. Journal Compilation © 2008, Wiley Periodicals, Inc.
Keywords: Bone healing; Hydroxyapatite; Osteoconductivity; Titanium scaffold